E-Cadherin: An Important Functional Molecule at Respiratory Barrier Between Defence and Dysfunction - Yuksel, Hasan; Ocalan, Merve; Yilmaz, Ozge (Frontiers in Physiology, 2021)
While breathing, many microorganisms, harmful environmental particles, allergens and environmental pollutants enter the human airways. The human respiratory tract is lined with epithelial cells that act as a functional barrier to these harmful factors and provide homeostasis between external and internal environment. Intercellular epithelial junctional proteins play a role in the formation of the barrier. E-cadherin is a calcium-dependent adhesion molecule and one of the most important molecules involved in intercellular epithelial barier formation. E-cadherin is not only physical barrier element but also regulates cell proliferation, differentiation and the immune response to environmental noxious agents through various transcription factors. In this study, we aimed to review the role of E-cadherin in the formation of airway epithelial barier, its status as a result of exposure to various environmental triggers, and respiratory diseases associated with its dysfunction. Moreover, the situations in which its abnormal activation can be noxious would be discussed.